Dietary flaxseed oil and fish oil ameliorates renal oxidative stress, protein glycation, and inflammation in streptozotocin-nicotinamide-induced diabetic rats - Jangale, Nivedita M.; Devarshi, Prasad P.; Bansode, Sneha B.; Kulkarni, Mahesh J.; Harsulkar, Abhay M. (Journal of Physiology and Biochemistry, 2016)
Protective and prophylactic effects of omega-3 fatty acids on oxidative stress and inflammation are well known. We assessed beneficial effects of flaxseed oil and fish oil on streptozotocin (65 mg/kg; i.p.)-nicotinamide (110 mg/kg; i.p.) induced diabetic rats by studying renal expression of antioxidant and inflammatory genes. Diabetic rats given 10 % flaxseed oil or 10 % fish oil diet for 35 days showed significant decrease in renal lipid peroxidation. Flaxseed oil diet resulted in up-regulation of renal superoxide dismutase-1 (SOD-1) (activity and expression) and glutathione peroxidase-1 (GPx-1) expression. Furthermore, both diets up-regulated catalase (CAT) (activity and expression) and down-regulated heme oxygenase-1 (HO-1) expression. Both diets were able to limit the renal advanced glycation end products (AGEs) formation and reduced receptor of AGE (RAGE) protein expression significantly. Expressions of interleukin-6 (IL-6) and NF-kappa B p65 subunit were down-regulated significantly by flaxseed oil or fish oil diet. The histological tubular injuries were also lowered by both diets. These results suggest that dietary omega-3 fatty acids may slow the progression of diabetic nephropathy (DN) associated with oxidative stress, glycation, and inflammation in the kidney.
Keywords: Diabetes; Fish oil; Flaxseed oil; Glycation; Kidney; Streptozotocin

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus